Time trends in diagnostic testing for primary ciliary dyskinesia in Europe. Issue 4 (24th October 2019) - Halbeisen, Florian S.; Shoemark, Amelia; Barbato, Angelo; Boon, Mieke; Carr, Siobhan; Crowley, Suzanne; Hirst, Rob; Karadag, Bulent; Koerner-Rettberg, Cordula; Loebinger, Michael R.; Lucas, Jane S.; Maitre, Bernard; et al.
Despite recent advances in diagnostic methods, diagnosis of primary ciliary dyskinesia (PCD) remains complex. We need a combination of different diagnostic tests, and all have their limitations [1]. In 2009, the first European Respiratory Society (ERS) Task Force on PCD in children published recommendations [2], suggesting that: 1) nasal nitric oxide (nNO) should be measured to screen for PCD in patients aged ≥5 years [3]; and 2) video microscopy (VM) analysis of ciliary beat pattern and frequency [4] plus electron microscopy (EM) [5] should be the key confirmatory diagnostic tests. Genetic testing was not recommended as part of the initial diagnostic testing, but as an additional test for inconclusive cases. The recommended test combination was nNO, VM and EM for patients aged ≥5 years and VM plus EM for younger patients. Adherence to the 2009 ERS task force diagnostic recommendations was low. To further improve PCD diagnosis, we must be more diligent and engaging in implementing the new evidence-based guidelines published in 2017. http://bit.ly/2zvjpBh